Next generation sequencing based targeted gene mutational profiles of formalin-fixed paraffin embedded specimens from colorectal carcinoma cases in Hospital Pakar Universiti Sains Malaysia - Afolabi, Hafeez Abiola (2025)
Colorectal carcinoma (CRC) is the third most prevailing cancer and the third most common cause of cancer-related deaths worldwide. It is a multistep process involving the accumulation of multiple genetic alterations. Through comprehensive molecular profiling and analysis of CRC using NGS, genetic mutations in colorectal cancer can be accurately identified for potential CRC screening. The present study carried out molecular analysis of formalin-fixed, paraffin-embedded (FFPE) specimens from 30 CRC cases in Hospital Pakar Universiti Sains Malaysia using NGS. Extracted gDNA from FFPE samples using a QIAgen FFPE extraction kit was used for library preparation, then sequenced in an Illumina MiniSeq machine. From a total of 30 FFPE samples [60% male and 40% female] sequenced, 22 completed the sequencing run, representing 73.3% of the samples: 20 CRC samples and 2 normal tissues. From demographics results, the highest data was recorded for “less than 65 years old” at 66.7%, “Retired group” at 70%, “Stage-3” at 53.3%, “Moderately differentiated grade” at 76.7%, and lastly, patients with “More than 2 comorbid” at 36.7%. Overall, 552 mutations involving 29 genes and 11 chromosomes were detected. The most upregulated were KIT:68(12.3%), FGFR4:61(11.1%), EGFR:60(10.9%), ALK:53(9.6%), DCUN1D1:41(7.4%), PDGFR:40(7.2%), KRAS:33(6.0%), CDK4:27(4.9%), and FGFR3:26(4.7%). Most downregulated gene mutations were ESR1, FGFR1, CCND1, HRAS, AR. The five most involved chromosome were chr4:(24.3%), chr7:(15.2%), chr12:(12.2%), chr5:(11.6%), and chr2:(11.1%) respectively. After applying filter criteria, 105 mutations involving 15 genes passed the filter. In-Silico Prediction model of clinical consequences of filtered mutations identified 21 pathogenic mutations (from 9 genes), 57 tolerated benign mutations (from 5 genes), and 17 variants unspecified (from 4 genes). Identified pathogenic gene mutations are APC, NRAS, ALK, PIK3CA, KRAS, IDH1, FGFR1, ERBB2, and ESR1. Validation of the pathogenic mutations on dbSNP, Ensembl, and Franklin by Genoox online databases also identified them as pathogenic genes. This is the first comprehensive NGS genetic profiling of CRC cases in Malaysia and HPUSM. The study’s novelty is based on the successful identification of pathogenic gene mutations in colorectal cancer cases in Malaysia and HPUSM. These findings will serve as a leadway for potential targeted therapy for CRC cases